PENGARUH MEDIA KOKORU TERHADAP KEMAMPUAN MOTORIK HALUS ANAK DI TAMAN KANAK-KANAK PEMBANGUNAN LABORATORIUM UNIVERSITAS NEGERI PADANG: THE EFFECT OF KOKORU MEDIA ON FINE MOTOR SKILLS OF CHILDREN AT PEMBANGUNAN LABORATORY KINDERGARTEN, STATE UNIVERSITY OF PADANG - Resa, Resa Tifeni Az-Zahra; Suryana, Suryana (Thufuli, 2023)
This research is motivated by the importance of developing children's fine motor skills in the Padang State University Laboratory Development Kindergarten. This study uses a quantitative approach in the form of Quasi Experiments. The population of this study were all students of the Padang State University Laboratory Development Kindergarten, with the sample being B2 and B3 classes, each of which consisted of 15 children. Data collection techniques that researchers use are oral tests, action tests and documentation. Data analysis techniques using normality test, homogeneity test, and hypothesis testing. Data collection tool used statement sheets. Then the data was processed by a difference test (t-test) using the SPSS 22.0 for windows application. Based on the results of research data analysis, the average pre test for the experimental class was 10.73 and for the control class was 10.53, while the post-test average for the experimental class was 15.07 and the control class was 12.27. Based on the pre-test and post-test data, the average gain score for the experimental class was 4.33 while the average gain score for the control class was 1.73. Based on the sig value (2-tailed) is 0.00